KEPRIBADIAN GURU MATEMATIKA YANG ISLAMI - Lailiyah, Maulidah (TADRIS: Jurnal Pendidikan Islam, 2018)
Abstract Teacher is one of profession that is recommended by Islam because teacherâ€™s duty are so precious. In Islam, the teacher not only do the learning, but also lead and give the studentsÂ a direction to the right way. As well as mathematic teacher who are not only assigned to deliver materials or mathematic lesson, but also should be able to guide the students in order to be always on the way that Allah blesses, and also be a good model for students. But the reality, some mathematic teachers have not been able to do the job professionally according to the shariâ€™a. They only carry out the duty because of financial demands. Therefore a strong religious foundation, a large Islamic knowledge, and a qualified teacherâ€™s personality competence are needed in order to carry out the task well. Key words: teacher; Islamic; personality